先化简,再求值;(a+b)/ab-4/(ab^2+a^2b),其中ab=15,a-b=2

来源:学生作业帮助网 编辑:作业帮 时间:2022/05/23 07:47:39
先化简,再求值;(a+b)/ab-4/(ab^2+a^2b),其中ab=15,a-b=2

先化简,再求值;(a+b)/ab-4/(ab^2+a^2b),其中ab=15,a-b=2
先化简,再求值;(a+b)/ab-4/(ab^2+a^2b),其中ab=15,a-b=2

先化简,再求值;(a+b)/ab-4/(ab^2+a^2b),其中ab=15,a-b=2
(1/ab)(a+b-4/(a+b))
ab=15 a-b=2
(a-b)^2=4
(a+b)^2=(a-b)^2+4ab=64
a+b=8 (ab=15>0,a-b=2>0 所以a+b>0)
(1/ab)(a+b-4/(a+b))=(1/15)(15/2)=1/2

(a+b)/ab-4/(ab^2+a^2b)
=(a+b)/ab-4/ab(a+b)
=1/ab(a+b-4/a+b)
=(a^2+b^2+2ab-4)/ab(a+b)
a-b=2则a^2+b^2-2ab=4.a^2+b^2+2ab=64
a+b=±8
原式=(64-4)/15*±8
=±1/2

因为ab=15 a-b=2
所以a=5 b=3或 a=-3 b=-5
(a+b)/ab-4/(ab^2+a^2b)
=(a+b)/ab-4/ab(a+b)
=[(a+b)^2-4]/ab(a+b)
(1)当a=5 b=3时
原式=(8^2-4)/15*8=1/2
(2)当a=-3 b=-5时
原式=[(-8)^2-4]/(-8)*15=-1/2